Basal Décollement Splaying Induces Mid‐Crustal Tectonic Imbrication in an Intracontinental Orogen. Issue 12 (9th December 2022) - Feng, Zhentian; Chu, Yang; Wei, Wei; Xue, Zhenhua; Xin, Guangyao; Meng, Lingtong; Zhang, Di; Lin, Wei
Abstract: Mid‐to‐lower crustal rock exhumation is common in orogenic belts, but the deformation process exposing these rocks remains debated. Distributed deformation in low viscous crust extruding mid‐to‐lower crustal rocks as channel flow and localized deformation along shear zones imbricating rigid blocks are two end‐members that account for crustal thickening and unroofing. At the northwest of the Early Paleozoic orogenic belt in the South China Block, the Jiuling Massif includes orogenic root rocks exhumed from deep crustal level. Their structural pattern and exhumation history can improve our understanding on how continental mid‐to‐lower crust is deformed, thickened, and finally transported to the surface. Structural analysis reveals that two major mid‐crustal ductile shear zones and their splays are developed at temperatures of ∼350°C–550°C. Anisotropy of magnetic susceptibility (AMS) shows that the Southern Jiuling Batholith has a modified AMS pattern by syn‐orogenic compression, suggesting a gradually deformed rigid block. Combining surface geological evidence and deep structures by gravity modeling, we find shear zones rooted in basal décollement incrementally stacked the rigid granitic blocks. Along strike, the major shear zones evolved differently with more splays at their eastern portions. Thus, tectonic imbrication can evolve to pervasive flow‐like deformation as shear zones continue to splay and form an anastomosed shear zone system. The complexed structures by splayed shear zones segmenting and imbricating small rigid blocks may correspond to the geophysically low‐velocity zone in the crust, so shear zone splaying is a linking mechanism between tectonic imbrication and viscous flow deformation of the crust. Key Points: A huge granitic batholith is segmented by ductile shear zones into granitic blocks, forming an imbricated crustal structure Mid‐crustal tectonic imbrication is induced by basal décollement splaying, responsible for the exhumation of mid‐to‐lower crustal rocks Splaying shear zones characterize the crust with seemingly flow‐like deformation pattern, responsible for mid‐to‐lower low‐velocity zones